Distal Radioulnar Joint Orientation and Lunate Morphology as Protective Factors of Symptomatic Idiopathic Ulnar Impaction Syndrome in Ulnar-Positive Variant Patients - Shin, Seong Kee; Kim, Ki Hong; Kim, Kyu Jin (Journal of Wrist Surgery, 2024)
Ulnar-positive variance is widely recognized as a risk factor for idiopathic ulnar impaction syndrome (UIS). However, not all patients with ulnar-positive variance progress to symptomatic UIS. Other factors, such as the shape of the lunate or the distal radioulnar joint (DRUJ), may also play a role. This study aims to elucidate the relationship between the shape of the lunate and the structure of the DRUJ and idiopathic UIS.A cohort of 40 cases diagnosed with idiopathic UIS (UIS group) and 87 control subjects with ulnar-positive variance but without symptoms were compared. Lunate shape was assessed by measuring the lunate type and radiolunate angle (RLA), whereas DRUJ morphology was evaluated using the sigmoid notch angle, DRUJ subluxation ratio, and DRUJ inclination. Independent t-tests were conducted to analyze differences in radiographic metrics between the two groups, and logistic regression analyses were used to examine risk factors for idiopathic UIS. Receiver operating characteristic curves were utilized to determine the cutoff values for statistically significant variables.Significant differences were observed between the two groups in terms of RLA, DRUJ subluxation ratio, and DRUJ inclination (p < 0.05). Logistic multiple regression analysis revealed a negative correlation between idiopathic UIS occurrence and both RLA (odds ratio [OR]: 0.92; 95% confidence interval [CI]: 0.87–0.96; p < 0.001) and the DRUJ subluxation ratio (OR: 0.01; 95% CI: 0–0.07; p = 0.002). Conversely, a positive correlation was found between UIS occurrence and DRUJ inclination (OR: 1.06; 95% CI: 1.01–1.12; p = 0.021).In patients with ulnar-positive variance, the incidence of symptomatic UIS decreases when the lunate extends more relative to the radius and when the DRUJ subluxation ratio increases or DRUJ inclination decreases.Level III, case–control study.
Keywords: ulnar impaction syndrome; ulnar-positive variance; lunate; distal radioulnar joint; protective factors